Measuring justice : primary goods and capabilities - Brighouse, Harry; Robeyns, Ingrid (Cambridge [England] ; New York : Cambridge University Press, 2010)
"This book brings together a team of leading theorists to address the question 'What is the right measure of justice?' Some contributors, following Amartya Sen and Martha Nussbaum, argue that we should focus on capabilities, or what people are able to do and to be. Others, following John Rawls, argue for focussing on social primary goods, the goods which society produces and which people can use. Still others see both views as incomplete and complementary to one another. Their essays evaluate the two approaches in the light of particular issues of social justice - education, health policy, disability, children, gender justice - and the volume concludes with an essay by Amartya Sen, who originated the capabilities approach"--Provided by publisher.
Machine generated contents note: 1. Social primary goods and capabilities as metrics of justice Ingrid Robeyns and Harry Brighouse; Part I. Theory: 2. A critique on the capability approach Thomas Pogge; 3. Equal opportunity, unequal capability Erin Kelly; 4. Justifying the capabilities approach to justice Elizabeth Anderson; 5. Two cheers for capabilities Richard Arneson; Part II. Applications: 6. Capabilities, opportunity, and health Norman Daniel; 7. What metric for justice for disabled people? Capability and disability Lorella Terzi; 8. Primary goods, capabilities, and children Colin MacLeod; 9. Education for primary goods or for capabilities? Harry Brighouse and Elaine Unterhalter; 10. Gender and the metric of justice Ingrid Robeyns; Part III. Concluding Essay: 11. The place of capability in a theory of justice Amartya Sen.
Includes bibliographical references and index.
Keywords: Social justice; Basic needs; Basic needs; Social justice